2007
DOI: 10.1126/science.1147880
|View full text |Cite
|
Sign up to set email alerts
|

A β-Defensin Mutation Causes Black Coat Color in Domestic Dogs

Abstract: Genetic analysis of mammalian color variation has provided fundamental insight into human biology and disease. In most vertebrates, two key genes, Agouti and Melanocortin 1 receptor (Mc1r), encode a ligand-receptor system that controls pigment type-switching, but in domestic dogs, a third gene is implicated, the K locus, whose genetic characteristics predict a previously unrecognized component of the melanocortin pathway. We identify the K locus as β-defensin 103 (CBD103) and show that its protein product bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
341
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(351 citation statements)
references
References 37 publications
6
341
1
3
Order By: Relevance
“…Candille et al (2007) recently showed that CBD103 is the long-sought-after Dominant Black (''K'') locus in dogs. The coat color of most mammals is largely determined by the ligand-receptor pair Agouti (Ag) and Melanocortin receptor 1 (MC1R).…”
Section: Discussionmentioning
confidence: 99%
“…Candille et al (2007) recently showed that CBD103 is the long-sought-after Dominant Black (''K'') locus in dogs. The coat color of most mammals is largely determined by the ligand-receptor pair Agouti (Ag) and Melanocortin receptor 1 (MC1R).…”
Section: Discussionmentioning
confidence: 99%
“…82 Of note, a mutation of a BD in dogs has been associated with coat colour. 83 This observation underscores the pleiotropic and sometimes unexpected functions of AMPs.…”
Section: Immunomodulatory Functionsmentioning
confidence: 84%
“…In addition to MSH, MC1R signaling is regulated by other soluble ligands, most notably agouti signaling protein (ASIP) which antagonizes MC1R signaling, decreases cAMP levels, and diminishes downstream melanocyte responses such as pigment induction 3, 4 . Recently, it has become clear that β-defensin 3 (BD3), known for its role in innate antimicrobial immunity, binds and influences MC1R signaling as a neutral MC1R agonist that blunts MSH-mediated MC1R activation as well as ASP-mediated MC1R antagonism 58 . Thus, BD3 may be an important regulator of MC1R-dependent melanocyte responses in the skin.…”
Section: Introductionmentioning
confidence: 99%